(untitled) (Journal of the College of Basic Education, 2022)
Asceticism developed since ancient times at the hands of the righteous until it reached the concept of spiritual mysticism, which scholars differed in its essence and what it is, but they agreed that the soul is a divine breath and a divine breath that humans perceive its effects and feel its results without knowing what it is, because it is the specialty of the Almighty, and man works to strengthen the connection between the conscience and the Creator, Glory be to Him, to reach the spiritual knowledge from which he derives a spirituality that transcends himself to the purity and beauty of virtuous humanity and makes him work in the necessities of maintaining the elements of this connection, so that in his sayings and poetry the knowledge of God Almighty and His attributes appear, and on this basis the study sheds light on a Sufi personality who lived in The third century AH, and these meanings were translated into the language of poetry in divine love. The research was based on an introduction, two axes, and a conclusion.